Implementation of the Prehospital Stroke Scale as a Stroke Attack Screening Tool for the High Risk Community - Kustanti, Cecilya; Widyarani, Linda (Fundamental and Management Nursing Journal, 2020)
Introduction: The process of changing a person into adolescence is a very important process where in adolescence, the process of finding the identity of a teenager is ongoing, looking for self-identity, trying new things, and social processes such as having a group of friends who he thinks have one hobby with him. Commonly referred to as "gangs", the characteristics of adolescents who are in the process of seeking their own identity often cause negative problems in their environment, including cyberbullying.Methods: In this systematic review, multiple databases were searched for articles that addressed our goal. We searched PubMed, EBSCO, Science Direct dan Google Scholar databases for articles that evaluated the performance of prehospital stroke scales. This literature review focuses on randomized control trial, cohort study dan qualitative study, published in the English language from 2010 to 2020.Results: Prehospital stroke scales with Cincinnati Prehospital Stroke Scale (CPSS), The Los Angeles Prehopsital Stroke Screen (LAPSS) and Face Arm Speech Time (FAST) time can advertisement campaign is widely used to promote population awareness of stroke warning signs and appropriate response.Conclusion: Promote population awareness of stroke warning signs and appropriate response.